Pengukuran Indeks Massa Tubuh pada Siswa SD Negeri Kaloran 2 Kabupaten Sragen - Fajar, Muhammad Salim; Indarto, Pungki (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to determine the body mass index of students of SD Negeri Kaloran 2 Sragen Regency. This research is a quantitative research with a descriptive approach. The sampling technique is carried out randomly, through research instruments data collection can be carried out, data analysis is quantitative . The subjects of this study are 72 students from first grade to sixth grade. The instruments used in this study include the measurement of body mass index guided by the Nusantara Student Fitness Test (TKPN). The results of the study showed that 12 students were categorized as undernourished, 42 students were categorized as well nourished, 12 students were categorized as overnourished and 6 students were categorized as obese. The conclusion, that the results of the body mass index of students of SD Negeri Kaloran 2 Sragen Regency are categorized as good nutrition. Keywords: Body mass index, fast food, good nutrition, obesity, physical fitness st food